Coverage and effectiveness of conditional cash transfer for people with drug resistant tuberculosis in Zimbabwe: A mixed methods study. - Collins Timire; Charles Sandy; Rashida A Ferrand; Regina Mubau; Peter Shiri; Obert Mbiriyawanda; Fredrick Mbiba; Rein M G J Houben; Debora Pedrazzoli; Virginia Bond; Nicola Foster; Katharina Kranzer (PLOS Global Public Health)
The End TB strategy recommends social protection to mitigate socio-economic impacts of tuberculosis. Zimbabwe started implementing a conditional cash transfer (CCT) programme for people on drug resistant tuberculosis (DR-TB) treatment in 2013. We aimed to determine the proportion of people receiving CCT and effectiveness of CCT in improving treatment outcomes, explore their experiences with registering for CCT and understand the impact of CCT from the perspective of beneficiaries. Data from 2014-2021 were extracted from TB registers and CCT payment records within the National TB Programme. Sixteen in-depth interviews were conducted with people who were completing treatment or had completed treatment within two months. Poisson regression, adjusted for province, year of treatment, age and sex was used to investigate associations between receiving CCT and successful treatment outcomes among people who were in DR-TB care for ≥3 months after treatment initiation. Qualitative data were analyzed using thematic analysis. A total of 481 people were included in the quantitative study. Of these, 53% (254/481) received CCT at some point during treatment. People who exited DR-TB care within three months were 73% less likely to receive CCT than those who did not (prevalence ratio (PR) = 0.27 [95%CI: 0.18-0.41]). Among those who were alive and in care three months after treatment initiation, CCT recipients were 32% more likely to have successful outcomes than those who did not (adjusted PR = 1.32, [95%CI: 1.00-1.75]). Qualitative results revealed lack of knowledge about availability of CCT among people with DR-TB and missed opportunities by healthcare providers to provide information about availability of CCT. Delays and inconsistencies in disbursements of CCT were frequent themes. CCT were associated with successful treatment outcomes. Improvements in coverage, timeliness and predictability of disbursements are recommended.